Severe bilateral isolated coronary ostial lesions as a rare manifestation of radiation-induced cardiac disease A case report. Issue 13 (March 2018) - Acharya, Metesh Nalin; El-Diasty, Mohammad; Schmack, Bastian; Weymann, Alexander; Mansur, Ashham; Popov, Aron-Frederik
Abstract: Rationale: With advances in contemporary radiotherapy techniques, and as cancer survival improves, severe isolated coronary ostial disease may develop many years following mediastinal radiotherapy, even in the absence of classical cardiovascular risk factors. Patient concerns: We describe the case of a 73-year-old woman with previous chest radiotherapy for breast cancer who underwent coronary artery bypass graft surgery for severe bilateral coronary ostial lesions. Diagnoses: Coronary angiography demonstrated severe, isolated bilateral coronary ostial lesions. Interventions: The patient underwent urgent coronary artery bypass graft surgery to treat her critical coronary artery disease. Outcomes: Intra-operatively, internal mammary arteries were not amenable to harvesting due to very dense mediastinal adhesions. Therefore, saphenous vein grafts were performed to the left anterior descending, distal left circumflex, obtuse marginal and distal right coronary arteries. The patient made a satisfactory in-hospital recovery, and was subsequently discharged back to her local hospital for rehabilitation. Lessons: Patients successfully treated with mediastinal radiotherapy require careful long-term follow-up for the assessment of radiation-induced coronary artery disease. Importantly, mediastinal irradiation may preclude internal mammary artery utilization, and thus alter the strategy for surgical myocardial revascularization.